A maize ribosome-inactivating protein is controlled by the transcriptional activator Opaque-2. - Bass, H W (1992)
Although synthesis of the cytosolic maize albumin b-32 had been shown to be controlled by the Opaque-2 regulatory locus, its function was unknown. We show here that b-32 is a member of the large and widely distributed class of toxic plant proteins with ribosome-inactivating activity. These ribosome-inactivating proteins (RIPs) are RNA N-glycosidases that remove a single base from a conserved 28S rRNA loop required for elongation factor 1 alpha binding. Cell-free in vitro translation extracts were used to show that both maize and wheat ribosomes were resistant to molar excesses of b-32 but not to the dicotyledonous RIP gelonin. We extracted RIP activity from kernels during seed maturation and germination. The amount of RIP activity increased during germination, although the amount of b-32 protein remained fairly constant. Expression of a maize RIP gene under the control of an endosperm-specific transcriptional regulatory may be an important clue prompting investigation of the biological basis for RIP expression in seeds of other plants.